PRIVATE CLOUD STORAGE IN RURAL'S MANAGEMENT AND INFORMATION SYSTEM USING ROADMAP FOR CLOUD COMPUTING ADOPTION (ROCCA) - Muhammad Agreindra Helmiawan; Irfan Fadil (INTERNAL (Information System Journal), 2020)
The draft Management Policy and Rural Information system are all articles with several articles governing all information security. In concerning Business Continuity Management it is written "The information system and security work unit backs up data periodically, to safer backing up data using Cloud computing facilities." Cloud computing has advantages as file management. Private cloud storage is a form of cloud computing that is intended for limited use in certain circles and one of its functions is used for backing up data or file management. On the other hand, there is software that can be used to implement private cloud storage, namely Owncloud. To run the Rural Information Security Policy Draft article on Business Continuity Management and for the provision of data centers, a study was conducted to implement private cloud storage using Owncloud. The method used in this study is the Roadmap for Cloud computing Adoption (ROCCA) with five stages, namely the stages of analysis, design, adoption, migration, and management. The results of this research are private cloud storage using Owncloud as a medium for storing, securing, and sharing files that are flexible and highly scalable that can be accessed via the internet by users.